2015
DOI: 10.1038/ejhg.2015.154
|View full text |Cite
|
Sign up to set email alerts
|

Mucolipidosis types II and III and non-syndromic stuttering are associated with different variants in the same genes

Abstract: Homozygous mutations in GNPTAB and GNPTG are classically associated with mucolipidosis II (ML II) alpha/beta and mucolipidosis III (ML III) alpha/beta/gamma, which are rare lysosomal storage disorders characterized by multiple pathologies. Recently, variants in GNPTAB, GNPTG, and the functionally related NAGPA gene have been associated with non-syndromic persistent stuttering. In a worldwide sample of 1013 unrelated individuals with non-syndromic persistent stuttering we found 164 individuals who carried a rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 14 publications
1
55
1
Order By: Relevance
“…Recently, it was found that persistent developmental stuttering unaccompanied by other deficits or symptoms can be linked to mutations in the lysosomal enzyme-targeting pathway (LETP) [6]. Mutations in the LETP pathway account for 9-16% of all cases of persistent nonsyndromic stuttering[7]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was found that persistent developmental stuttering unaccompanied by other deficits or symptoms can be linked to mutations in the lysosomal enzyme-targeting pathway (LETP) [6]. Mutations in the LETP pathway account for 9-16% of all cases of persistent nonsyndromic stuttering[7]. …”
Section: Introductionmentioning
confidence: 99%
“…The mannose 6-phosphate is added to these acid hydrolases in a two-step process carried out by the products of three genes. Mutations in all three of these genes have been found in humans who stutter [6, 7]. However, the mechanisms by which mutations in an apparent “housekeeping gene” produce a deficit with the remarkable specificity of stuttering remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in GNPTG result in an attenuated form of ML disease (mucolipidosis IIIgamma; MLIIIgamma) and, like the other genes within this pathway, have also been associated with persistent stuttering (2,1115). The γ subunit contains an MRH (mannose-6-phosphate receptor homology) domain similar to those found in ER glucosidase II (16).…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral speech behaviors associated with stuttering are intermittent and range in expression from part-syllable repetitions and audible/ inaudible sound prolongations to inconsistencies during perceptually fluent speech (e.g., increased kinematic variability, reduced articulatory rate). Genetic predispositions may form the basis for stuttering and stuttering behaviors in at least a small subset of people who stutter (Kang et al, 2010;Raza et al, 2016); however, the factors that underlie stuttering within and across individuals are not well understood.…”
mentioning
confidence: 99%